Peculiarità della funzione cautelare nel diritto canonico alla luce dei provvedimenti ex can. 1722 CIC (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. Natura e tipologia dei provvedimenti cautelari ex can. 1722 CIC - 3. Le esigenze cautelari contemplate dalla disposizione del can. 1722 CIC - 4. Questioni interpretative sulle misure analizzate - 5. Funzione cautelare e diritto canonico.AbstractSpecificity of the precautionary function in canon law in the light of the canon 1722 CIC measuresIn canon law, the existence of a precautionary function, under the competence of the Ordinary, can be deduced from an analysis of the measures mentioned in can. 1722 CIC. Such a function is specifically aimed at protecting the peculiar requirements of canon law, and it is strictly connected with the ultimate goal of the salus animarum. It also takes on unique characteristics as a result of the relationship which binds the faithful of the ecclesial community; such a relationship is due, in turn, to the divine origin of a legal system which members of a religious group participate in because of a sacramental investiture.
Keywords: Diritti delle religioni